PEMBELAJARAN ONLINE SEBAGAI BENTUK PENGUATAN PENDIDIKAN SELAMA PANDEMI COVID-19 DI SD MUHAMMADIYAH 03 KOTA MEDAN - SIREGAR, EKO FEBRI SYAHPUTRA; DAMILIA, EVA (Unversitas Katolik Santo Thomas, 2020)
Covid 19 Pandemic brought change in every field without exception the education sector, especially learning that occurred in elementary schools. This study aims to describe the strengthening of education during the covid-19 pandemic at SD Muhammadiyah 03 Medan City, activities carried out by students while studying online at home, various obstacles that students may face in online learning activities and efforts made in overcoming various obstacles students face during online learning. This type of research is qualitative research. The type of data in this study is qualitative data. The results of this study in the form of mandatory activities in the form of online learning by SD Muhammadiyah 03 Medan students who use the WhatsApp application in carrying out teaching and learning activities online. The learning activity in question starts with filling in attendance / attendance, asking news / checking the situation of students, giving directions before giving assignments, doing assignments and collecting assignments according to the schedule and hours specified. This activity is one of the solutions that can be done in elementary schools in carrying out teaching and learning activities online with the hope that students will continue to learn even if they have to be at home.